KEWENANGAN DEWAN KEHORMATAN PENYELENGGARA PEMILU DALAM PEMBERHENTIAN KOMISIONER KPU DAN BAWASLU DI INDONESIA (Studi Pada Bawaslu Propinsi Sumatera Utara) - Abdullah Arkam (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
The birth of the Election Organizing Honorary Council as one of the institutions which tasked with creating and overseeing a democratic election process is a new history and an important breakthrough in the political system in this country. The presence of the Election Organizing Honorary Council is expected to be able to give new hope for the creation of a democratic election. In addition, it is being able to create elections that fulfill a sense of fairness, credibility, accompanied by integrity of implementation. The Election Organizers Honorary Council in the dismissal of General Elections Commission and Election Supervisory Agency is regulated in Law Number 15 of 2011 concerning General Election Organizers. The Election Organizers Honorary Council not only takes action against members of election organizers who are clearly proven to have violated the election code of ethics, but also provides sanctions for the ranks of the secretariat of election organizers through their respective superiors based on the disciplinary provisions of the staffing code of ethics.  Based on the discussion, it was concluded that the mechanism for imposing sanctions against General Elections Commission and Election Supervisory Agency given by the Election Organizing Honorary Council is that if there are complaints and reports or recommendations, they can be submitted to the Election Organizers Honorary Council to examine and decide on alleged violations of the Code of Ethics. Complaints or reports are submitted accompanied by at least 2 (two) pieces of evidence and after fulfilling administrative verification, the Election Organizers Honorary Council convenes to determine and prove the report or complaint. The legal consequences of the decision of the Election Organizing Honorary Council in dismissing the commissioners of General Elections Commission and Election  Supervisory Agency are final and binding so that no other legal remedies or further legal remedies are available after the Election Organizers Honorary Council decision takes effect since it was stipulated and pronounced in an open plenary session. The decision is immediately binding and coercive in nature so that all institutions administering state power and including judicial bodies are bound and obliged to carry out the Election Organizers Honorary Council decision as it should. Keywords: Authority, Election Organizers Honorary Council, Dismissal.